Respon Tanaman Bawang Merah Pada Beberapa Jarak Tanam Dalam Pola Tanam Tumpangsari Dengan Jagung - Muhsanati Muhsanati; Rintan Putri Demara; Gustian Gustian (Proceedings Series on Physical & Formal Sciences, 2021)
The implementation of intercropping is one alternative that can be done to increase the diversity of crops cultivated by farmers, due to the increasing activity of land conversion and limited ownership. The practices of growing several types of crops on the same land and time can provide several advantages. The plantation of corn and shallot on the same field and at the relatively same time will contribute to meet the community's needs for food and feed, especially during the current covid-19 pandemic. The use of various spacing of shallot within corn plantations is expected to increase income and land-use efficiency. The results showed that narrow space of shallots (10 cm × 15 cm) gave a higher unit area yield, and a wider space (20 cm × 20 cm) gave a higher land equivalence ratio comparing to other plant spacing (10cm × 15cm, and 10cm × 20cm).